A Voltage Controlled Oscillator Using IGZO Thin-Film Transistors - Keragodu, Tejaswini (2018)
early career research grant with project ref. ECR/2017/000931. National Funds through FCT - Portuguese Foundation for Science and Technology POCI-01-0145-FEDER-007688